Assessing the inclusiveness of growth in Africa: Evidence from Cameroon, Senegal, and Tanzania - Georges Vivien Houngbonon; Arthur Bauer; Abdoulaye Ndiaye; Clara Champagne; Tite Yokossi; Nathalie Ferrière; Hédi Brahimi; Jeanne Avril (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this study, we assess the inclusiveness of growth by tracking the yearly percentage change in the household consumption of individuals over different growth spells in Cameroon, Senegal, and Tanzania. With cross-sectional data, we track the consumption of groups of individuals that share similar time-invariant characteristics, consistent with the pseudo-panel methodology. When the panel data are available, we track the consumption of each individual in order to generate the non-anonymous growth incidence curve. We find that the standard growth incidence curve does not always help to detect or to identify the winners and the losers from the growth process. In addition, the more educated individuals are not necessarily the ones that benefit from growth, except in Tanzania where growth is driven by the skill-intensive sectors. We also find significant losers from growth in Tanzania where the rate of inflation is very high compared to the other countries. Our methodology finds that 63 per cent of the population in Tanzania live in households whose real consumption expenditures fall during the growth spell.
Keywords: O10; O15; O43; O55; 330; inclusive growth; Africa; poverty; inequality